Nanomechanics with plasmonic nanoantennas: Ultrafast and local exchange between electromagnetic and mechanical energy - Bragas, Andrea Veronica (2023)
Converted into mechanical nanoresonators after optical pulsed excitation and electron decay into coherent acoustic phonons, plasmonic nanoantennas produce a periodic modulation of their optical properties, allowing, in turn, an optical reading of these extremely small movements. In this work, we review the physics of these nanoresonators and their acoustic vibrations, whose frequencies are in the range of a few to tens of GHz. The accurate determination of their oscillation frequencies allows them to act as mechanical nanoprobes, measure local mechanical moduli of the environment, and perform high-resolution imaging using phononic reconstruction. Furthermore, the internal and external damping mechanisms that affect the quality factor of the nanoresonator and, in particular, the role of the substrate when the nanoantennas are integrated into platforms and probed individually are also reviewed. Finally, we discuss the all-optical generation of hypersonic surface acoustic waves with nanoantennas and the importance of their manipulation for potential acousto-plasmonic devices operating in the GHz range and at nanoscale.